'A Consequential Ill that Freedom Draws'. Intellectual Property and Authorial Visibility in the Case of Jacob Voegen van Engelen versus his Publishers. - Baggerman, Arianne (Quaerendo)
This article focuses on the field of tension between eighteenth-century publishers and 'their' scholarly or semi-scholarly authors working on commission at a time when there was no legislation on intellectual property rights. A case in point is the struggle that arose in 1779 between Jacob Voegen van Engelen – editor of the first Dutch medical periodical – and his publishers Pieter Blussé and Willem Holtrop. They came into conflict after van Engelen's defection – along with a number of authors and the concept of the Genees-, natuur-, en huishoudkundige Jaarboeken – to another publisher. The conflict was fought out in both the old and the new medical journal and in newspaper advertisements. The arguments adduced by both parties offer an interesting view of the trap that kept eighteenth-century scholarly or semi-scholarly authors imprisoned: their reputation benefited from keeping up the appearance of altruism, i.e. the pretence of writing for the public benefit, but they depended for their existence on the royalties their publishers had to pay them on a regular basis. In the case of Voegen van Engelen we learn how his publishers Holtrop and Blussé shrewdly exploited this paradox. They tried to disqualify van Engelen both as a scholar and as a man of letters by scathingly calling him a hack: that is, someone who writes for his living and who is therefore denied any claim to any rights in intellectual property.